Essential management skills for pharmacy and business managers - De Silva, Titus (Boca Raton, Florida : CRC Press, 2013)
The books describes the kinds of things that will most often go wrong in organizations of all types and sizes and provides proven methods for resolving these issues. It explains how to develop and implement an effective quality management system in the pharmacy or a retail operation that complies with external standards.
Managing Professionals -- Management Theories -- Managing a Pharmacy -- Managing Change -- Managing Risk -- Problem Solving -- Conflict Resolution -- Managing Stress at Work -- Team Building -- Effective Communication -- Leadership -- Effective Delegation -- Empowerment -- Motivation -- Managing Cultural Diversity at Work -- Performance Review -- Quality Management Systems -- Quality Management System for Pharmacy Practice -- Audits and reviews -- Dispensing errors and near misses -- Patient complaints.
Includes bibliographical references and index.
Keywords: PHARMACY ADMINISTRATION